Activation of IGF-1 and Insulin Signaling Pathways Ameliorate Mitochondrial Function and Energy Metabolism in Huntington’s Disease Human Lymphoblasts - Naia, Luana (2015)
Huntington's disease (HD) is an inherited neurodegenerative disease caused by a polyglutamine repeat expansion in the huntingtin protein. Mitochondrial dysfunction associated with energy failure plays an important role in this untreated pathology. In the present work, we used lymphoblasts obtained from HD patients or unaffected parentally related individuals to study the protective role of insulin-like growth factor 1 (IGF-1) versus insulin (at low nM) on signaling and metabolic and mitochondrial functions. Deregulation of intracellular signaling pathways linked to activation of insulin and IGF-1 receptors (IR,IGF-1R), Akt, and ERK was largely restored by IGF-1 and, at a less extent, by insulin in HD human lymphoblasts. Importantly, both neurotrophic factors stimulated huntingtin phosphorylation at Ser421 in HD cells. IGF-1 and insulin also rescued energy levels in HD peripheral cells, as evaluated by increased ATP and phosphocreatine, and decreased lactate levels. Moreover, IGF-1 effectively ameliorated O2 consumption and mitochondrial membrane potential (Δψm) in HD lymphoblasts, which occurred concomitantly with increased levels of cytochrome c. Indeed, constitutive phosphorylation of huntingtin was able to restore the Δψm in lymphoblasts expressing an abnormal expansion of polyglutamines. HD lymphoblasts further exhibited increased intracellular Ca(2+) levels before and after exposure to hydrogen peroxide (H2O2), and decreased mitochondrial Ca(2+) accumulation, being the later recovered by IGF-1 and insulin in HD lymphoblasts pre-exposed to H2O2. In summary, the data support an important role for IR/IGF-1R mediated activation of signaling pathways and improved mitochondrial and metabolic function in HD human lymphoblasts.